Parsimonious Motivational Factors for Participation in Sporting Events : A Review - Sen, Subhasis (Indian Journal of Marketing, 2020)
The purpose of the study was to explore the parsimonious motivational factors among sponsors while organizing sporting events and discuss the rationale behind event participation among spectators for the interest of sponsors investing in global sports events. The research study undertaken is a viewpoint using content analysis, considering inductive qualitative data and is exploratory in nature. Parsimonious motivational factors were derived based on the responses of spectators watching international sporting events backed by secondary data collected from research articles and case studies pertaining to sports event attendance behaviour and sponsorships. Qualitative data collected both from primary as well as secondary sources were used for content analysis. It was observed that sports events result in two types of involvement, mainly participation and attendance, which are influenced by economic, sociological, psychological, and motivational factors like age, leisure time, family size, health and weight concerns, personal growth, and affiliation. It was also observed that experiential sponsorship activation (ESA) reflects dimmersive brand experiences and encourages high levels of active participation. The results suggested parsimonious motives behind participation of spectators and sponsors in mega sporting events. The study revealed that relevant messaging, choice-based ticket pricing, flexibility, and accessibility across platforms attracted more viewership. Fan engagement through social networking sites leads to branding of event sponsors.